Laser beam melting process based on complete-melting energy density for commercially pure titanium. (September 2019) - Kim, Hyung Giun; Kim, Won Rae; Kwon, Ohyung; Bang, Gyung Bae; Ham, Min Ji; Park, Hyung-Ki; Jung, Kyung-Hwan; Kim, Kang Min; Lee, Chang-Woo; Kim, Gun-Hee
Highlights: Study of laser beam melting (LBM) process parameter based on the thermodynamical complete-melting energy density for CP-Ti. Microstructural study was conducted to understand the change in the part's density and porosity. The diverse effects of the LBM process parameters, such as high density and porous structure, were confirmed. Abstract: Laser beam melting (LBM) based on the complete-melting energy density for commercially pure titanium (CP-Ti) was investigated. Process parameters were set corresponding to the thermodynamically calculated energy density for full melting of CP-Ti. From the calculated energy density, power of 50–250 W and scan speed of 371–1855 mm/s were derived with the fixed other conditions. Microstructural study on formation of pores was conducted to understand the change in part's density. Fundamental study with wide range of LBM process parameters, particularly based on the complete-melting energy density, could confirm the effects like high density and porous structure.